Antibodies and Vaccines Target RBD of SARS-CoV-2 - Min, Long; Sun, Qiu (Frontiers in Molecular Biosciences, 2021)
The novel human coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which gives rise to the coronavirus disease 2019 (COVID-19), has caused a serious threat to global public health. On March 11, 2020, the WHO had officially announced COVID-19 as a pandemic. Therefore, it is vital to find effective and safe neutralizing antibodies and vaccines for COVID-19. The critical neutralizing domain (CND) that is contained in the receptor-binding domain (RBD) of the spike protein (S protein) could lead to a highly potent neutralizing antibody response as well as the cross-protection of other strains of SARS. By using RBD as an antigen, many neutralizing antibodies are isolated that are essential to the therapeutics of COVID-19. Furthermore, a subunit vaccine, which is based on the RBD, is expected to be safer than others, thus the RBD in the S protein is a more important target for vaccine development. In this review, we focus on neutralizing antibodies that are targeting RBD as well as the vaccine based on RBD under current development.